How the BRAF V600E Mutation Defines a Distinct Subgroup of Colorectal Cancer: Molecular and Clinical Implications - Catherine E. Bond; Vicki L. J. Whitehall (Gastroenterology Research and Practice)
The BRAF oncogene is an integral component of the MAP kinase pathway, and an activating V600E mutation occurs in 15% of sporadic colorectal cancer. This is an early event in serrated pathway tumourigenesis, and the BRAF V600E has been commonly associated with the CpG island methylator phenotype, microsatellite instability (MSI), and a consistent clinical presentation including a proximal location and predilection for elderly females. A proportion of the BRAF mutant lesions remain as microsatellite stable (MSS), and in contrast to the MSI cancers, they have an aggressive phenotype and correlate with poor patient outcomes. Recent studies have found that they have clinical and molecular features of both the BRAF mutant/MSI and the conventional BRAF wild-type cancers and comprise a distinct colorectal cancer subgroup. This review highlights the importance of the BRAF mutation occurring in colorectal cancer stratified for molecular background and discusses its prognostic and clinical significance.